2017
DOI: 10.1016/j.spmi.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the power conversion efficiency of perovskite solar cells with different materials as Hole-Transport Layer by numerical simulations

Abstract: In this paper, a theoretical study of different p-p-n perovskite solar cells has been performed by means of computer simulation. Effects of the offset level upon the power conversion efficiency (PCE) of these devices have been researched using five different materials such as spiro-OMeTAD, Cu2O, CuSCN, NiO and CuI, as Hole Transporting Layer (HTL). The Solar Cells Capacitance Simulator (SCAPS)-1D has been the tool used for numerical simulation of these devices. A strong dependence of PCE has been found with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(42 citation statements)
references
References 26 publications
(37 reference statements)
1
41
0
Order By: Relevance
“…The simulation results revealed that Cu 2 O‐based solar cell showed the champion efficiency of ≈25%. The author further predicted the TiO 2 /CH 3 NH 3 PbI 3 /Cu 2 O device with an efficiency of 28% by introducing a p‐type perovskite with zero VB offset (VB difference between Cu 2 O and perovskite) …”
Section: Inorganic Hole Transporting Materials In Pscsmentioning
confidence: 99%
“…The simulation results revealed that Cu 2 O‐based solar cell showed the champion efficiency of ≈25%. The author further predicted the TiO 2 /CH 3 NH 3 PbI 3 /Cu 2 O device with an efficiency of 28% by introducing a p‐type perovskite with zero VB offset (VB difference between Cu 2 O and perovskite) …”
Section: Inorganic Hole Transporting Materials In Pscsmentioning
confidence: 99%
“…Since the first report in 2009, organometal halide perovskites have been attracting much attention owing to their large absorption coefficient, high carrier mobility, and tunable bandgap . With continuous efforts in perovskite compositions, fabrication processes and device configurations, the certified power conversion efficiency (PCE) of perovskite solar cells (PSCs) has reached an astonishing record of 25.2% . Generally, a planar PSC device is composed of a perovskite layer as light absorber sandwiched between electron and hole selective contacts.…”
Section: Introductionmentioning
confidence: 99%
“…In very recent years, significant research activities were devoted to the development of PSCs, focusing on different areas, including device structures, film deposition techniques, perovskite chemical composition, electron transfer layers, and engineering of HTMs. However, the theoretical value for power conversion efficiency of perovskite solar cells is 30% and it shows the great future of these category of solar cells . In this work, we have reviewed the recent progress of perovskite solar cells using different dopant‐free HTMs.…”
Section: Introductionmentioning
confidence: 99%